Homes Appliances Control Using Bluetooth - Jamil Alsayaydeh, Jamil Abedalrahim; Syed Salim, Syed Najib; Wong, Adam Yoon Khang; Indra, Win Adiyansyah; Mohamed, Njikam; Pellipus, Christina; Shkarupylo, Vadym (Asian Research Publishing Network, 2019)
New technology applications in managing human living styles, workplaces including residences have led to the discovery of different methods of interacting and controlling both users and the buildings. This piece of research work proposed a simpler system for users' interaction with home appliances, using Bluetooth technology for operation support. As a study for this article, a combination of the Bluetooth and Arduino modules with smartphones is introduced to provide building users with easier access and control through a simple user interface. This designing way showed also great management flexibility compared to using switches. Controlling remotely home users and appliances is more convenient to its residents. Home appliances can be easily monitored using smartphones via Bluetooth connectivity because each one can communicate over nearer cellular networks using some built-in communication capabilities. This paper discussed about a combination of Android software and hardware, with Bluetooth module and smartphones. Then, it explained how these technologies set together have created a system that enables accessing a control unit to turn "ON/OFF" status of the home devices. The concluding sections are about the design and implementation of the proposed model applying these technologies.